Tuberkulosis Serviks pada Penderita Tuberkulosis Paru: [Cervical Tuberculosis in Pulmonary Tuberculosis Patient] - Renny Irviana Eka Tantri; Ida Bagus Ngurah Rai (Faculty of Medicine Universitas Airlangga, 2016)
Background: Tuberculosis (TB) is a disease caused by infection of Mycobacterium tuberculosis complex. Global Tuberculosis Report 2011 stated the incidence of TB cases reached 8.7 million (1.1 million co-infected with HIV) and 990,000 people died because of TB. Twenty five percent of extrapulmonary TB occurs in cervix, which is 0.1 to 0.65% of all TB cases, and 5-24% of TB in urogenital tract. Case: We report the case of a woman, aged 28 years admitted with complaint hematuria since 6 months. With UTI treatment, Patient didn’t get improved. Gynecology examination within normal limit. The results of cervical biopsy were granulomatous chronic inflammation with suppuratif inflammatory process. Patient were diagnose with cervical TB. Patiens also complaint chronic cough with decrease of appetite and night sweating. Chest x-ray showed Lung TB with thickening of upper left pleural. AFB sputum examination with positive result, patient diagnosed with Lung TB. Patient got therapy ATD first chategory and after 2 weeks of therapy patient showed clinical improvement. Conclusion: Cervical TB is more common in women of childbearing age between 20-40 years. In this case, the possibility of Cervical TB occurs because through hematogenous dissemination of pulmonary tuberculosis.